1995
DOI: 10.1161/01.res.76.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Ca 2+ Sensitivity of Skinned Cardiac Muscle Contractility Coincident With Troponin T–Band Shifts in the Diabetic Rat

Abstract: We have measured the apparent Ca2+ sensitivities of force development in skinned cardiac trabeculae at different sarcome lengths together with shifts in troponin (Tn) T subunits on specimens from the same hearts and drawn insights into the pathogenesis of myocardial dysfunction in the diabetic rat. The Ca(2+)-force relations were measured at a long (2.4-microns) and a short (1.9-microns) sarcomere length. In disease, compared with the control condition, the apparent Ca2+ sensitivity was greatly diminished at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 36 publications
5
57
0
Order By: Relevance
“…MLC1v and MLC2v) or thin filament proteins (Fig. 1A), confirming previously published findings (Averyhart-Fullard et al 1994;Schiaffino & Reggiani, 1996;Akella et al 1997). Since the cardiac myofibrillar effects of thyroid deficiency are limited to changes in the expression of MHC isoforms, any alterations in contractile properties in skinned myocardium may be attributed to altered MHC expression.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…MLC1v and MLC2v) or thin filament proteins (Fig. 1A), confirming previously published findings (Averyhart-Fullard et al 1994;Schiaffino & Reggiani, 1996;Akella et al 1997). Since the cardiac myofibrillar effects of thyroid deficiency are limited to changes in the expression of MHC isoforms, any alterations in contractile properties in skinned myocardium may be attributed to altered MHC expression.…”
Section: Resultssupporting
confidence: 91%
“…It is interesting to note that while cardiac MHC expression varies with thyroid state, altered levels of triiodothyronine (T×) do not appear to alter the phenotypic expression of other myofibrillar protein isoforms, such as the thin filament proteins troponin I (TnI) and troponin T (TnT) (Averyhart-Fullard et al 1994;Akella et al 1997). However, it is well known that thyroid state markedly affects the Ca¥ handling properties of the sarcoplasmic reticulum (SR) (Kiss et al 1994).…”
mentioning
confidence: 99%
“…Isoform appearance is developmentally regulated: cTnT 3 predominates, while cTnT 4 is a minor (fetal) isoform in the adult human heart; the additional two fetal isoforms, cTnT 1 and cTnT 2 , are also present, but are barely detectable (86,87). Different studies have suggested that a significant amount of cTnT 4 is re-expressed in failing myocardium (84,85,87), which exhibits decreased myofibrillar ATPase activity (80,81,83) and a decrease in Ca 2+ sensitivity (88,89). Changes in the variable region of the cTnT molecule can alter interactions in the troponin complex; this may explain how a shift in cTnT isoforms alters myocardial contractility and Ca 2+ sensitivity of the cardiac contractile proteins (66,86).…”
Section: Myofibrillar Assembly In Congestive Hfmentioning
confidence: 99%
“…Modulating muscle power output appears to provide the ecologically important ability to operate at different points along a tradeoff between performance and energetic cost. S triated muscles from a variety of taxa show substantial interand intra-specific variation in the sensitivity of myosin crossbridge activation by calcium (1)(2)(3)(4)(5)(6). Within individual animals, calcium sensitivity of muscle activation varies during ontogeny, training, and disease and appears to be one of the primary ways that striated muscles adjust to changes in contractile regimes (7)(8)(9).…”
mentioning
confidence: 99%
“…Troponin T (TnT), one of the components of the troponin-tropomyosin complex, varies in isoform composition during development (14)(15)(16)(17), training (18), and human heart failure (19,20). Changes in TnT isoform composition frequently correlate with variation in the calcium sensitivity of myosin cross-bridge activation (1)(2)(3)(4)(5)(6)(7)(8)(9), and experimental manipulations of TnT isoform composition have been shown to affect the calcium sensitivity of actomyosin ATPase (21). Point mutations in human cardiac TnT alter both calcium sensitivity and myosin cross-bridge kinetics (22,23).…”
mentioning
confidence: 99%